PERUBAHAN GAYA HIDUP MAHASISWA JURUSAN SOSIOLOGI UNIVERSITAS NEGERI MALANG DENGAN HADIRNYA BUDAYA POPULER JEPANG - Muhammad Rizal Hifandi Jusuf; Devina Agustya Ulin Nikma; Imarotul Mahbubah; Nurlita Eka Paluvy; Salsabilla Hana Surya (Universitas Negeri Makassar, 2022)
This article was created with the aim of analyzing the students of the Department of Sociology Education, State University of Malang who are fond of Japanese popular culture, namely watching anime. This Japanese popular culture is indeed very popular among teenagers. The process of entry is so fast among the younger generation, making this trend very popular. Not only in Indonesia, this anime is popular, but in various parts of the world you may be familiar with the term